The effect of combined Action Observation Therapy with eccentric exercises in the treatment of mid-portion Achilles-tendinopathy: a feasibility pilot randomised controlled trial - Deirdre Ryan; Gráinne O'Donoghue; Ebonie Rio; Ricardo Segurado; Cliona O'Sullivan (BMC, 2022)
Abstract Background Mid-portion Achilles Tendinopathy (AT) is a common musculoskeletal condition with varying rehabilitation success rates. Despite the prevalence of this condition, a considerable proportion of individuals experience persisting pain and functional deficits. Current treatment approaches bias the biomedical model which emphasises physically treating and loading the tendon. Overall, there is a lack of consideration for the central nervous system that is commonly implicated in chronic injuries. The aim of this pilot study was to explore the feasibility of combining Action Observation Therapy (AOT), a treatment technique which targets central changes and influences motor learning, with eccentric exercises in the treatment of mid-portion AT. AOT involves the observation of movements and is commonly followed by the physical performance of these same movements. Methodology This was a double-blinded randomised controlled pilot feasibility study. All participants underwent the 12-week Alfredson eccentric training protocol. The intervention group watched videos of the exercises prior to performing these exercises, whilst the control group watched nature videos before performing the same exercises. Study feasibility was the primary outcome measure, with the Victorian Institute of Sports Assessment- Achilles (VISA-A) selected as the primary clinical outcome measure. Results Thirty participants were recruited, reflecting a 75% eligibility rate and 100% of eligible participants enrolled in the study. The retention rate at week 12 was 80%. At week six the mean VISA-A score improved by 18.1 (95% CI 10.2-26.0) in the intervention group and 7.7 (95% CI 0.3-14.9) in the control group, and 75% and 33% of participants in the intervention and control group respectively exceeded the minimal clinically important difference (MCID). At week 12 the mean VISA-A score from baseline improved by 22.25 (95% CI 12.52-31.98) in the intervention group and 16.5-(95% CI 8.47-24.53) in the control group, equating to 75% and 58% in each group respectively exceeding the MCID. Conclusion The positive feasibility outcomes and exploratory data from the clinical outcome measures suggest that a larger scaled RCT is warranted to further investigate the impact of AOT in the rehabilitation of mid-portion AT. Trial registration ISRCTN58161116, first registered on the 23/12/2020.